The Effect of Job Performance, Education and Training and Work Experience on Employee Career Development - Novelia Asita Mranani; Supartini; Endang Muryani (Journal of Economy, Accounting and Management Science (JEAMS), 2020)
Employees in general have the potential to make a good contribution to the company, therefore human resources (HR) become one of the important production factors in a company in achieving its goals. Each organization or company continues to strive to improve the performance of its human resources. The more qualified and high-performing human resources, the higher the company's performance and company goals can be achieved properly. The purpose of this study is to determine the effect of work performance, education and training and work experience simultaneously and partially on the career development of employees of PT. ISS Indonesia Area National Hospital Surabaya. The sample of this research is the employees of PT. ISS Indonesia Area National Hospital Surabaya, with a total sample of 60 respondents. The analysis technique uses Multiple Linear Regression with SPSS programs or software. The results showed that jointly (simultaneously) showed that work performance, education and training and work experience affect employee career development, partially work performance has a positive and significant effect on employee career development, while partially education & training and work experience has no positive and significant impact on employee career development.